The phase 1/2 ACCEPT trial: concurrent cetuximab and intensity modulated radiation therapy with carbon ion boost for adenoid cystic carcinoma of the head and neck - Adeberg, Sebastian; Akbaba, Sati; Uzun-Lang, Kristin; Held, Thomas; Verma, Vivek; Nikoghosyan, Anna; Bernhardt, Denise; Münter, Marc; Freier, Kolja; Plinkert, Peter K.; Hauswald, Henrik; Herfarth, Klaus; et al. (International journal of radiation oncology, biology, physics, 2020)
Purpose - The adenoid cystic carcinoma (ACC), Erbitux, and Particle Therapy (ACCEPT) phase 1/2 trial (NCT01192087) evaluated a combined-modality approach (concurrent cetuximab and intensity modulated radiation therapy with carbon ion boost) for newly diagnosed nonmetastatic head and neck ACC. - Methods and Materials - Twenty-three patients with ACC were enrolled between June 2012 and June 2017 after initial diagnosis or postoperatively. All received a 400 mg/m2 cetuximab loading dose a week before radiation therapy, followed by weekly 250 mg/m2 doses starting on the first day of radiation therapy. The carbon ion radiation therapy boost was 24 Gy (relative biological effectiveness) in 8 daily fractions, followed by intensity modulated radiation therapy (54 Gy). The primary endpoint was safety and feasibility (defined based on Common Terminology Criteria for Adverse Events grade ≥3 events). Secondary endpoints included local and distant relapse, disease-free survival, and overall survival. - Results - Disease was most commonly in the paranasal sinuses (30%), palate (17%), and nasopharynx (17%). Nine (39%) patients underwent surgery (R1: 22%, R2: 78%). Median follow-up was 38.5 months. No patients experienced grade 4 to 5 events. Rates of grade 3 rash and radiation dermatitis were 17% and 22%, respectively. Grade 2 and 3 mucositis and dysgeusia occurred in 43% and 48% and in 9% and 0%, respectively. Grade 2 to 3 dysphagia and xerostomia were present in 43% and 4% and in 26% and 0%, respectively. At last follow-up, 5 (22%) patients experienced in-field relapse and 6 (26%) developed distant metastases. The 3-year disease-free survival was 67%, and median overall survival was 54 months. - Conclusions - Outcomes of this trial were satisfactory. Although the trial did not meet the predefined criteria of feasibility owing to the comparatively high rates of grade 3 dermatitis, numbers are comparable to existing data on cetuximab + radiation therapy.